2014
DOI: 10.1371/journal.pone.0104688
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Proteins Associated with the Interior and Exterior of Vesicular Stomatitis Virus Virions

Abstract: Virus particles (virions) often contain not only virus-encoded but also host-encoded proteins. Some of these host proteins are enclosed within the virion structure, while others, in the case of enveloped viruses, are embedded in the host-derived membrane. While many of these host protein incorporations are likely accidental, some may play a role in virus infectivity, replication and/or immunoreactivity in the next host. Host protein incorporations may be especially important in therapeutic applications where l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…It is well established that retroviruses package host lysyl-tRNA synthetase (LysRS) by contact with Gag, which targets tRNA to prime transcription to DNA upon infection of a new host ( 6 ). Host factors have also been previously observed in virus particles, such as influenza virus ( 7 ), vesicular stomatitis virus ( 8 ), vaccinia virus ( 9 ), and herpes simplex virus ( 10 ) (reviewed in reference 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that retroviruses package host lysyl-tRNA synthetase (LysRS) by contact with Gag, which targets tRNA to prime transcription to DNA upon infection of a new host ( 6 ). Host factors have also been previously observed in virus particles, such as influenza virus ( 7 ), vesicular stomatitis virus ( 8 ), vaccinia virus ( 9 ), and herpes simplex virus ( 10 ) (reviewed in reference 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The recombinant viruses VSV-p53wt and VSV-p53-CC were previously engineered using the VSV-ΔM51 backbone and were previously described in detail (37). Purified virus was obtained exactly as described previously (105). Plaque-isolated viruses were obtained by isolating individual viral plaques, which were then amplified on BHK-21 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Evolution has forced viruses to develop diverse mechanisms to avoid or delay destruction by the complement system [6]. To our knowledge, this article is the first to report that CD59 proteins are associated with IBV virions, although parainfluenza virus 5, mumps virus, vesicular stomatitis virus and NDV have been found to be associated with complement regulators through their envelopes [23][24][25][26][27]. Proteomic analysis of IBV particles has demonstrated that dozens of host proteins are present in the purified IBV virions, but CD59 was not detected [22,28].…”
mentioning
confidence: 87%